Systems analysis of grass cell wall biosynthesis for biofuel production - Lin, Fan (My University, 2017)
Grass cell walls play an important role in plant development, pathogen defense, and are an abundant and sustainable carbon source for biofuel production. Chapter 1 introduces the great impact of cell wall composition on the major biomass-based biofuel technologies, biochemical and thermal conversion. To further improve biomass conversion efficiency by manipulating cell walls genetically, it is important to understand the molecular basis of cell wall synthesis and regulation. However, current understanding of grass cell wall synthesis lags behind that of dicots, despite the great compositional difference between them. In this dissertation, I apply “omics” methods to further our knowledge of cell wall synthesis during grass development and demonstrate that genetic manipulation of cell walls can potentially improve thermal conversion. In Chapter 2, we examine the cell wall composition and the transcripts of 65 putative cell wall synthesis genes in 30 rice samples from different organs at 10 developmental time points. A method is developed to identify candidate cell wall synthesis genes, based on the correlations between cell wall abundance and gene expression. We establish hypotheses for nine candidate genes that may synthesize cell wall components like xylans, mixed linkage glucan, and pectins. The cell wall profile also provides a baseline for evaluating the variation of cell wall composition. In Chapter 3, we perform proteomics, cell wall profiling, and metabolite profiling on a rice elongating stem internode. With LC-MS/MS, we detect a total number of 2356 proteins in this internode. Many of them are glycosyltransferases, acyltransferases, glycosylhydrolases, cell wall-localized proteins, and protein kinases from families that may function in cell wall biosynthesis or remodeling or regulation. The presence of these proteins is consistent with active cell wall synthesis in this internode, as indicated by cell wall assays. This study fills the void of shotgun proteomics data in rice stems and provides the basic information for a more detailed multi-omics experiment on internode segments. Chapter 4 is a proof of principal study demonstrating that genetic manipulation of cell wall structures can improve the efficiency of thermal conversion. A major challenge for thermal conversion, thermal products with various chemical natures can not be upgraded to fuels with a simple catalytic strategy. One solution, known as thermal fractionation, is to collect different thermal products separately at different conversion temperatures, which depends on the different thermal stability of cell wall components. The efficiency of thermal fractionation can be improved by altering the thermal stability of cell wall components. We hypothesize that lignin thermal stability will increase in a switchgrass knock-down mutant of caffeic acid O-methyltransferase, which has less S- lignin subunits that can not form strong linkages at C-5 position. The elevation of lignin thermal stability will lead to a better segregation lignin-derived products from polysaccharide-derived products. Indeed, the results indicate that the mutant yields less lignin-derived products at a low conversion temperature, at which most polysaccharides are converted. In conclusion, Chapter 2 and Chapter 3 develop an analysis method and a technical method for systems study of cell wall synthesis and identify a set of cell wall synthesis candidates for functional study. Understanding the function of more novel cell wall synthesis genes will provide more targets to manipulate cell wall structures. As a result, there will be more opportunities to improve thermal fractionation efficiency other than the example we show in Chapter 4.
Keywords: Cell wall; Biofuel; Grasses